Digital database training to support school management - Herfina Herfina; Sri Setyaningsih; Triningsih Triningsih (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
One of the challenges and important aspects in supporting the implementation of school management is the availability of a comprehensive and integrated digital database. However, there are still obstacles in development and development directions that still need to be managed optimally. Therefore, it is necessary to manage a digital database that can be accessed by students, teachers and school principals online. The aim is to conduct an initial study of digital database management to support school management. This Community Service was carried out by school principals, teachers and school operators in Limo District, Depok City to improve data-based planning initiated by the Ministry of Education and Culture. Data-based planning training is carried out in two stages, namely coaching & discussion, action in the form of training and evaluation. The process is carried out in 5 steps, namely (1) a session starting from the self, (2) a concept exploration session, (3) a comprehension elaboration session, (4) contextual demonstration sessions, and (5) an action plan preparation session. The results of the service show that Data-Based Planning Activities have had a good impact on School Principals, Teachers, and School Operators, and no obstacles were found in their implementation.   Abstrak Salah satu tantangan dan aspek penting dalam mendukung pelaksanaan manajemen sekolah adalah tersedianya pangkalan data digital yang komprehensif dan terintegrasi. Namun masih terdapat kendala dalam pembangunan dan arah pengembangan yang belum terkelola secara optimal. Oleh karena itu perlu tata Kelola pangkalan data digital yang dapat di akses oleh siswa, guru, dan kepala sekolah secara online. Tujuannya ialah sebagai studi awal tata kelola pangkalan data digital untuk menunjang manajemen sekolah. Pengabdian Kepada Masyarakat ini dilakukan pada Kepala Sekolah, guru, dan operator sekolah se Kecamatan Limo Kota Depok dalam upaya peningkatan perencanaan berbasis data yang dicetuskan oleh Kemendikbudristek. Pelatihan Perencanaan Berbasis data dilakukan melalui dua tahap, yaitu coaching & diskusi, tindakan berupa pelatihan serta evaluasi. Prosesnya dilakukan melalui 5 langkah, yaitu (1) sesi mulai dari diri; (2) sesi eksplorasi konsep; (3) sesi elaborasi pemahaman; (4) sesi demonstrasi kontekstual; dan (5) sesi penyusunan rencana aksi. Hasil pengabdian menunjukkan Kegiatan Perencanaan Berbasis Data memberikan dampak yang baik bagi Kepala Sekolah, Guru dan Operator Sekolah serta tidak ditemukan kendala dalam pelaksanaannya Kata Kunci: Pangkalan data digital; pelatihan; perencanaan berbasis data